Alternative voices : essays on contemporary vocal and choral composition - Anhalt, István (University of Toronto Press, 1984)
Istvan Anhalt, himself a composer of many vocal works, has written an interdisciplinary study of the innovative vocal and choral music that has emerged in Europe and North America since the Second World War. This music has amazed, confused, sometimes shocked, and often deeply moved its listeners, and the author probes its very roots. Anhalt sketches briefly the antecedents of this revolutionary music and then illustrates the subject by looking closely at works by three of the greatest composers of modern vocal and choral music: Luciano Berio's Sequenza III for female solo voice, GyÓ§rgy Ligeti's Nouvelles Aventures for three solo voices and small instrumental ensemble, and Witold Lutoslawski's Trois Poèmes d'Henri Michaux for large chorus and orchestra. The author next seeks to formulate a conceptual framework to explain post-war vocal composition. He discusses relationships between poetry and music, speaking and singing, theatre and music, and composers and performers. He identifies and examines recurring themes in his corpus, including hallowed and cursed names, repetition as a mythical and/or mystical technique, the arcane, magical elements in music and language, and music as spectacle or celebration and as a search for the past. Anhalt also considers the structural elements and compositional procedures used in creating this type of music. The complex associations with other creative activities that typify modern vocal composition help to make it, as Anhalt shows clearly, an extraordinary rich mosaic of alternative voices.